Peranan pembelajaran project based learning (PjBL) dalam bentuk short movie terhadap peningkatan kualitas layanan bimbingan klasikal - Nur’aeni, Nur’aeni; Rosepyanti, Dewi; Zahra, Samhana; Rahmadani, Muhammad; Situmorang, Dominikus David Biondi (Indonesian Institute for Counseling, Education and Theraphy, 2022)
Generation Z, known as the digital generation, was born in the era of rapid technological development. The main characteristics of Generation Z are the tendency towards instant things and dependence on the internet and technology. In this context, education plays an important role in preparing the next generation who are able to adapt to changing times. Through a 21st century learning approach, learners are encouraged to develop 4C skills: critical thinking, communication, collaboration, and creativity. One approach used is project-based learning, where learners engage in problem-solving investigations and produce real products. The use of short movie media allows learners to engage directly with problem situations, facilitating in-depth analysis. Based on literature reviews from various research journals, it shows that making short films can make learning more meaningful. The practice of using short movie media in classical tutoring also received a positive response from students. The integration of this media can improve the quality of learning and the overall learning experience of learners.